Standardization of skin cleansing in vivo: part II. Validation of a newly developed Automated Cleansing Device (ACiD). Issue 2 (4th September 2013) - Sonsmann, F. K.; Strunk, M.; Gediga, K.; Schliemann, S.; Seyfarth, F.; Elsner, P.; Diepgen, T. L.; Kutz, G.; John, S. M.
<x xml:space="preserve">Abstract</x> Background Skin cleansers for occupational use are manufactured for different types and degrees of soiling without common, legally binding requirements for product testing. This leads to different, manufacturer‐specific test methods and a lack of comparable information on skin cleansing products. Objectives The aim of this investigation was to validate a newly developed standardized automated cleansing device (ACiD) for in vivo evaluation of industrial skin cleansers. Methods Two ACiD were tested regarding the intra‐ and inter‐device specific reproducibility of test results. Results Skin cleansing process carried out by the three independent washing modules which constitute an ACiD‐unit and two separate ACiD‐units led to highly comparable results. There was no significant difference between the washing modules or between the two separate ACiD‐units detected. Only different parameter settings resulted in significantly different detergency. Conclusions Intra‐ and inter‐device specific test results of an in vivo model of skin cleansing using the automated cleansing device (ACiD) were reproducible. The long‐term aim is a standardized classification of occupational skin cleansing products comparing their skin cleansing effectiveness in relation to their skin irritancy. This might then provide the basis for a rational specific product selection by consumers and may be used as a tool for future product development by manufacturers.